Biology and significance of circulating and disseminated tumour cells in colorectal cancer - Steinert, Gunnar; Schölch, Sebastian; Koch, Moritz; Weitz, Jürgen (Langenbeck's archives of surgery, 2012)
Purpose: More than 130 years ago, circulating tumour cells (CTCs) and disseminated tumour cells (DTCs) have been linked to metastasis. Since then, a myriad of studies attempted to characterise and elucidate the clinical impact of CTCs/DTCs, amongst others in colorectal cancer (CRC). Due to a flood of heterogeneous findings regarding CTCs/DTCs in CRC, this review aims to describe the known facts about CTC/DTC biology and clinical impact. Methods: To identify the basic scientific literature regarding the biology and clinical impact of CTCs/DTCs in CRC, we reviewed the literature in the PubMed database. We focused on publications written in English and published until January 2012. As search terms, we used “colorectal cancer (CRC)”, “colon cancer (CC)”, “CTC”, “DTC”, “bone marrow (BM)”, “lymph node (LN)”, “peripheral blood (PB)”, “significance” and “prognosis”. Results: CTC detection and quantification under standardised conditions is feasible. Several studies in large patient settings have revealed prognostic impact of CTCs in CRC. CRC-derived DTC detection and analysis in BM exhibits a more heterogeneous picture but also shows clinical value. Furthermore, the presence of DTCs in LN has a strong prognostic impact in CRC. Conclusions: Clinical relevance and prognostic significance of CTCs/DTCs in CRC have been clearly demonstrated in many experimental studies. The major challenge in CTC/DTC research is now to harmonise the various identification and detection approaches and consequently to conduct large prospective multi-institutional trials to verify the use of CTCs/DTCs as a valid prognostic and predictive biomarker for clinical routine.
Gesehen am 21.09.2018